Pengaruh Produk Wisata dan Kebijakan Harga terhadap Minat Kunjungan Wisatawan - Dewi, Kartika (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2019)
The purpose of this research is to know the Influence of Tourism Product and Pricing Policies to Tourist Interest in Taman Buah Mekarsari Bogor. This research is descriptive-verifikative type, while the sampling technique used is incindental sampling with 100 respondents. The technique of data analysis used is multiple linear regression analysis. From the statistical test result, it was known that tourism product positively and significantly effect to tourist interest and pricing policy also had positive and significant influence to tourist, besides tourism product and pricing policy influence to tourist interest in Taman Buah Mekarsari equal to 68.8%.